Economics in America an immigrant economist explores the land of inequality - Deaton, Angus (Princeton University Press, 2023)
"From the Nobel Prize-winning economist and New York Times-bestselling coauthor of Deaths of Despair and the Future of Capitalism, candid reflections on the economist's craftWhen economist Angus Deaton immigrated to the United States from Britain in the early 1980s, he was awed by America's strengths and shocked by the extraordinary gaps he witnessed between people. Economics in America explains in clear terms how the field of economics addresses the most pressing issues of our times-from poverty, retirement, and the minimum wage to the ravages of the nation's uniquely disastrous health care system-and narrates Deaton's own account of his experiences as a naturalized US citizen and academic economist.Deaton is witty and he pulls no punches. In this incisive, candid, and funny book, he describes the everyday lives of working economists, recounting the triumphs as well as the disasters, and tells the inside story of the Nobel Prize in economics and the journey that led him to Stockholm to receive one. He discusses the ongoing tensions between economics and politics-and the extent to which economics has any content beyond the political prejudices of economists-and reflects on whether economists bear at least some responsibility for the growing despair and rising populism in America.Blending rare personal insights with illuminating perspectives on the social challenges that confront us today, Deaton offers a disarmingly frank critique of his own profession while shining a light on his adopted country's policy accomplishments and failures"--